Experimental Investigation on Mix Proportion Design for Foam Concrete - K. , Chaitanya Kumar; H. , Thiagu (International Journal of Psychosocial Rehabilitation, 2020)
An experimental investigation is done on finding the design mix proportion for foam concrete. Foam concrete is lightweight concrete made with cement, fine aggregates, and foam. Coarse aggregates are not used. It has excellent properties like low density and fire resistance. Using foam concrete in constructions, it reduces dead loads on structures and foundations and lowers labor costs during construction. In foam concrete, the foam is produced from a foam generator. The equipment that also helps in foam production is an air compressor. In this, the right amount of foam density can be adjusted. The foam generator has a single-phase motor inside the machine, and it also contains an inlet valve, an outlet valve, and a pressure valve. The various mix designs are prepared using fine aggregate, cement, and different percentages of foam. The foam is prepared using a protein-based foaming agent. These foaming agents create air bubbles. These air bubbles reduce the surface tension. Various trial mixes are prepared, and the compressive strengths are calculated. The right trial mix with more compressive strength is selected.